2014
DOI: 10.1063/1.4872268
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission from ZnO nanoparticles

Abstract: Room temperature single photon emitters are very important resources for photonics and emerging quantum technologies. In this work we study single photon emission from defect centers in 20 nm zinc oxide (ZnO) nanoparticles. The emitters exhibit bright broadband fluorescence in the red spectral range centered at 640 nm with polarized excitation and emission. The studied emitters showed continuous blinking, however, bleaching can be suppressed using a polymethyl methacrylate (PMMA) coating. Furthermore, hydrogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 27 publications
3
72
1
Order By: Relevance
“…SPSs in ZnO defects are advantageous in terms of its visibility and stability. It has been shown that the red fluorescence of ZnO defect center is almost fully linearly polarized with high visibility (~85%) [8]. This is highly beneficial for employing SPSs for quantum communications as the information is encoded in the polarization state of the emitter.…”
Section: Single-photon Sources (Spss) From Znomentioning
confidence: 97%
See 4 more Smart Citations
“…SPSs in ZnO defects are advantageous in terms of its visibility and stability. It has been shown that the red fluorescence of ZnO defect center is almost fully linearly polarized with high visibility (~85%) [8]. This is highly beneficial for employing SPSs for quantum communications as the information is encoded in the polarization state of the emitter.…”
Section: Single-photon Sources (Spss) From Znomentioning
confidence: 97%
“…The calculated decay rates correspond to radiative lifetimes ranging from 1 to 5 ns and non-radiative lifetimes ranging from 40 to 429 ns, respectively. Choi et al showed that only 10% of the observed emitters showing strong bunching behavior and emission from those defects was associated with a very narrow emission line [8]. However, Jungwirth et al showed that 7 of the 14 nanoparticle-based defects studied displayed signs of bunching and one of the five sputtered film defects exhibited bunching [10].…”
Section: Single-photon Sources (Spss) From Znomentioning
confidence: 99%
See 3 more Smart Citations